Territorializing/decolonizing South American prehistory: Pedra Furada and the Cerutti Mastodon. Issue 1 (1st January 2019) - Turnbull, David
ABSTRACT: South American rock art and prehistory with all its controversies is a rich site for exploring the processes of territorialization through which humans shape their understanding of the world in their earliest movements through the environment, and also for examining how narratives of prehistory are woven. The paper examines the debate over the Cerutti Mastodon and why Serra da Capivara, one of the largest rock art complexes in the world, remains in analytic limbo. It suggests that rethinking these two examples may offer a possible way out of some of the analytic difficulties in South American prehistory through a decolonizing approach to understanding the reasons for the rejection of the Cerutti Mastodon, and the lack of recognition of Serra da Capivara's most important site – Bocqueirã da Pedra Furada (PBF).